Performance evaluation of a counter-rotating vertical axis wind turbine (VAWT) on a moving train - MD Zin, Muhammad Fariq; Didane, Djamal Hissein; Ogab, Mohammed; M Elfaghi, Abdulhafid; Afolabi, Lukmon Owolabi (Penerbit UTHM, 2020)
Renewable energies are the types of energy that always exist and environmentally friendly. Wind energy is one of the renewable energy types that can reduce the mass use of fossil fuels as an alternative way to generate electricity. Practically, the Wind turbine is responsible for converting the kinetic energy as the wind act on the blades to generate electrical energy. In this study, the Savonius-type counter-rotating wind turbine has been chosen to study its aerodynamic performance on a moving train. For the simulation, the wind velocities tested start from 50 km/h until 160 km/h with 10 km/h interval between each case while investigating the performance in terms of torque and power output. The designs of the models are developed using Solidworks software and the Computational Fluid Dynamics (CFD) simulation software; ANSYS FLUENT was sued to run the simulations. The simulation results such as velocity streamlines, velocity contours, pressure contours and turbulent kinetic energy have been captured to allow the reader to observe the flow applied on the train as well as a wind turbine. The results obtained from the simulation show that the aerodynamic performance in terms of both power and torque output increases as the wind speed on the blades increases.